What if the FARC Demobilizes? - Enzo Nussio; Kimberly Howe (Stability : International Journal of Security and Development, 2012)
In September 2012, the Colombian government officially announced ongoing peace talks with the leftist Revolutionary Armed Forces of Colombia (FARC). This gesture was the first of its kind since the failed negotiation process with the same guerrilla group during the government of Andrés Pastrana (1998–2002) (see Villarraga 2009). The FARC remains the largest and strongest non-state armed group operating in the country, and can be traced back to as early as 1964. Observers of the current negotiations are largely optimistic about the prospects for peace and the end of the decades-long conflict.